The Influence Of Product Quality, Brand Image, And Product Design On The Purchase Decision Of Vans Shoes (A Study On The Solo Community) - Kusnadi Kusnadi; Pemilia Sulistiawati (Business, Accounting, and Knowledge Journal, 2025)
This study aims to determine and analyze the direct influence of lifestyle on product purchasing decisions at Masyarakat Solo, to determine and analyze the direct influence of brand image on product purchasing decisions at Masyarakat Solo, to determine and analyze the direct influence of product value on product purchasing decisions at Masyarakat Solo and to determine and analyze the simultaneous influence of lifestyle, brand image, product value on product purchasing decisions at Masyarakat Solo. This study uses a quantitative method with a sample of 50 consumer respondents at Masyarakat Solo. Data were analyzed using validity tests, reliability tests, multicollinearity tests, heteroscedasticity tests, normality tests, multiple linear regression analysis tests, T tests, F tests, R2 determination coefficient tests using IBM SPSS Statistics. The results of the study indicate that lifestyle directly has a significant effect on product purchasing decisions for consumers at Masyarakat Solo, product value directly has a significant effect on product purchasing decisions for consumers at Masyarakat Solo, brand image have a significant effect on product purchasing decisions for consumers at Masyarakat Solo, and directly and simultaneously lifestyle, brand image, and product value have a significant effect on consumer product purchasing decisions at Masyarakat Solo.